Singlet oxygen induced mutation spectrum in mammalian cells. - de Oliveira, R C (1992)
In order to characterize the molecular nature of singlet oxygen (1O2) induced mutations in mammalian cells, a SV40-based shuttle vector (pi SVPC13) was treated with singlet oxygen arising from the thermal decomposition of the water-soluble endoperoxide of 3,3'-(1,4-naphthylidene) dipropionate (NDPO2). After the passage of damaged plasmid through monkey COS7 cells, the vector was shuffled into E. coli cells, allowing the screening of supF mutants. The mutation spectrum analysis shows that single and multiple base substitutions arose in 82.5% of the mutants, the others being rearrangements. The distribution of mutations within the supF gene is not random and some hotspots are evident. Most of the point mutations (98.4%) involve G:C base pairs and G:C to T:A transversion was the most frequent mutation (50.8%), followed by G:C to C:G transversion (32.8%). These results indicate that mutagenesis in mammalian cells, mediated by 1O2-induced DNA damage, is targeted selectively at guanine residues.